Bridge Pier Scour Evaluation in Meandering Channels - Elsaeed, Gamal; Elsersawy, Hossam; Ibraheem, Mohammad; Samir, Fatma (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2015)
The objectives of this research are to predict and evaluate the effect of releasing high/extreme flow discharges on scour at 13 bridge piers of (3) bridges located at Kafr El-Zayat City. Field data, empirical equations and a two-dimensional model were used. The empirical equations were used to predict the general, contraction and bend scour of the bed's morphological changes along the entire reach of the osetta Branch. The 2-D model was used to predict scour at the bridge piers in the study area considering two scenarios of high river discharges. The expected extending of the scour holes around the main piers was also predicted. The results showed that in case the released discharges were (69.90, 220.00m.m3/day), the total scour around piers evaluated at the (3) bridges were (13.98, 17.74m) for bridge No. (1), (10.33, 13.93m) for bridge No. (2) and (12.64, 15.34m) for bridge No. (3). It is recommended to follow up the geometry of the scour holes after one year of passing extreme high discharges.